2015
DOI: 10.1007/s00392-015-0821-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-vitamin K antagonist oral anticoagulants in the cardioversion of patients with atrial fibrillation: systematic review and meta-analysis

Abstract: This systematic review and meta-analysis suggests that NOACs may be as safe as VKAs in the setting of AF cardioversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
2
15
0
3
Order By: Relevance
“…One such retrospective cohort study by Yadlapati et al found shortterm therapy with rivaroxaban and dabigatran to be safe in AF patients undergoing cardioversion [21]. In the same vein, two studies that need mention are those by Briasoulis et al [22] and Caldeira et al [23]. The advantage of this study over the abovementioned studies is the use of the ''random effects model'', which provides a stronger methodology in the case of meta-analyses.…”
Section: Safety Outcomesmentioning
confidence: 90%
“…One such retrospective cohort study by Yadlapati et al found shortterm therapy with rivaroxaban and dabigatran to be safe in AF patients undergoing cardioversion [21]. In the same vein, two studies that need mention are those by Briasoulis et al [22] and Caldeira et al [23]. The advantage of this study over the abovementioned studies is the use of the ''random effects model'', which provides a stronger methodology in the case of meta-analyses.…”
Section: Safety Outcomesmentioning
confidence: 90%
“…Результаты, полученные в нашей работе, со-относятся с результатами других исследователей [15][16][17][18][19][20], однако во многих из них оценка конеч-ных точек проводилась на 30-90-е сутки [15,17]. В нашем же исследовании наблюдение продол-жалось до 1 года после проведения электричес-кой кардиоверсии.…”
Section: неинвазивная аритмологияunclassified
“…Habár több klinikai vizsgálat és metaanalízis kimutatta, hogy a rivaroxabankezelés ugyanolyan hatékony és biztonságos, mint a warfarin, acenokumarol vagy dabigatran [3,4], amint azt esetünk is mutatja, közepes thromboemboliás rizikóval bíró pitvarfibrilláló betegekben rivaroxabanterápia mellett is kialakulhat intracardialis thrombus [5].…”
Section: Esetismertetésunclassified